The more the merrier – experimental evidence for density-dependent feeding facilitation in the bird-specialised tick Ixodes arboricola. Issue 3 (March 2016) - Van Oosten, A.R.; Matthysen, E.; Heylen, D.J.A.
Graphical abstract: Highlights: We investigated the effects of density-dependent feeding in a tick with strong dependence on individual hosts. Attachment success and engorgement weight were unaffected, but more ticks were recovered at higher feeding densities. Our results indicate that aggregated feeding may increase tick performance despite strong dependence on individual hosts. This has important consequences for tick population dynamics and pathogen transmission. Abstract: Similar to many other parasites, the distribution of ticks among hosts is strongly skewed, with few hosts harbouring the majority of parasites. Because parasite-induced impairment of host health, parasite population growth and pathogen transmission are density-dependent, understanding why tick distributions are skewed is important for the population and evolutionary dynamics of both parasite and host. However, there is currently no knowledge concerning parasites that strongly depend on individual hosts. Here, we investigated the effects of tick density on feeding performance in the nidicolous tree-hole tick, Ixodes arboricola, which feeds on cavity-nesting birds and is the carrier of several tick-borne pathogens. Nidicolous ticks reside in or close to their hosts' nests and therefore depend strongly on individual hosts and their offspring. Increased feeding success at higher densities (facilitation) may therefore be detrimental to the ticks themselves. We investigated the effects of tick density on feeding performance of I. arboricola by infesting great tit nestlings with one to five adult ticks, which is within the natural range. There was no effect of tick density on initial attachment success, attachment after 48 h or engorgement weight, but tick recovery rates increased significantly with tick density. We also found a modest increase in nestling body mass with tick density, suggesting that birds over-compensate resource drainage by the ticks and, by doing this, anticipate the costs of a tick-rich environment. Our results indicate that nidicolous ticks perform better when feeding in aggregation. This may have important consequences for population dynamics and consequently pathogen transmission.